Effect of early childhood education programme on cognitive development of young children in Oyo State (2015)
The study investigated the effect of early childhood education on primary school pupils’ cognitive achievement. Two hypotheses were postulated. The sample consisted of one hundred public primary two school pupils randomly selected from six schools within Akinyele Local Government Area in Ibadan, Oyo State, Nigeria. Fifty of the sampled pupils had preschool education and fifty pupils did not attend pre-school. The two validated instruments used to collect the data were English Studies Achievement Test (ES AT)=.62 and Mathematics Achievement Test (MAT)=.71 respectively to assess the cognitive ability of the pupils. The data collected were analyzed using t-test. The study found that pupils who attended preschool performed better in English Language (t=5.07, df=98;p<0.05 ) and Mathematics ( t=4.06, df=98;p<0.05) tests than pupils who did not attend pre-school. It is therefore recommended among others that parents and all education stakeholders should invest confidently in this level of education and take full advantage of pre-school programme and facilities for their children’s development and life-long learning.